The Effect of Self-Efficacy and Life Satisfaction on Job Performance With Work Engagement as a Mediating Variable - Iqbal Rassaldi; Vini Wiratno Putri (Universitas Negeri Semarang, 2024)
This study aims to analyze the mediating role of work engagement in the relationship between self-efficacy, life satisfaction, and job performance at PLN UID Central Java and Yogyakarta. The population in this study consists of employees of PLN UID Central Java and Yogyakarta, with a sample of 100 respondents selected using proportionate random sampling. The results show that work engagement mediates the effect of self-efficacy on job performance, but does not mediate the effect of life satisfaction on job performance. Furthermore, life satisfaction was found to have no significant effect on job performance. The R-square value indicates that 42.2% of the variance in job performance is explained by other variables. Future research is expected to examine additional independent variables influencing performance and to consider alternative mediating variables, as work engagement was only able to partially mediate the relationship between self-efficacy and performance and was unable to mediate the relationship between life satisfaction and performance.